2008
DOI: 10.1002/cbic.200800271
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Dicing of Guanosine‐Rich shRNAs by Quadruplex‐Binding Compounds

Abstract: RNA interference is triggered by small hairpin precursors that are processed by the endonuclease dicer to yield active species such as siRNAs and miRNAs. To regulate the RNAi-mediated suppression of gene expression, we imagined a strategy that relies on the sequence-specific inhibition of shRNA precursor processing by immediate RNA-small molecule interactions. Here, we present a first step in this direction by augmenting shRNAs with guanosine-rich sequences that are prone to fold into four-stranded structures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 63 publications
0
26
0
Order By: Relevance
“…18,19 In a further study, we used quadruplexes as small-molecule-addressable sequences for the regulation of dicer-mediated processing of G-rich shRNAs. 32 In order to better judge the stabilities of RNA quadruplexes, we have carried out a comparative study by investigating DNA and RNA quadruplex sequences in the absence and presence of the monovalent ions potassium and sodium which are known to stabilize quadruplexes by coordination with the 6-oxo-functionality of the tetrad-forming guanosines.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 In a further study, we used quadruplexes as small-molecule-addressable sequences for the regulation of dicer-mediated processing of G-rich shRNAs. 32 In order to better judge the stabilities of RNA quadruplexes, we have carried out a comparative study by investigating DNA and RNA quadruplex sequences in the absence and presence of the monovalent ions potassium and sodium which are known to stabilize quadruplexes by coordination with the 6-oxo-functionality of the tetrad-forming guanosines.…”
Section: Introductionmentioning
confidence: 99%
“…While technically challenged, the success in identification of miR-21-specific inhibitor could shed light on the feasibility of the chemical biology approach in this regard [39]. Besides potentially targeting the protein(s) involved in the regulation of selective miRNAs processing, several small molecules could directly bind to RNAs, including miRNAs [42][43][44][45]. Given the diversity of RNA secondary structures among miRNA precursor population, it is plausible to speculate that small molecules targeting specific pri-, pre-or mature miRNA could be identified.…”
Section: Perspectives On the Chemical Biology Approach To Tnai/mirna mentioning
confidence: 99%
“…Several small molecules have been reported that directly bind to RNAs (65,66), including miRNAs (67,68). Helixthreading peptides were discovered, which consist of an acridine core that acts as a RNA-duplex intercalator, which is flanked by short peptides (e.g., N-Ser-Val-acridine-Arg-C) (67).…”
Section: Small Molecules That Directly Interact With Mirnasmentioning
confidence: 99%
“…However, no pre-miR-39 binding of the compound has been demonstrated to date. In another report, an shRNA-targeting luciferase was modified with a G-rich loop and three additional Gs at the 5′ end, in order to enable potential G-quadruplex formation (68). Even though no evidence for actual G-quadruplex formation of this oligomer was provided, a set of classical G-quadruplex small molecule binders were screened for their ability to inhibit processing of the shRNA.…”
Section: Small Molecules That Directly Interact With Mirnasmentioning
confidence: 99%